Site‐Specific Dynamics of β‐Sheet Peptides with DPro–Gly Turns Probed by Laser‐Excited Temperature‐Jump Infrared Spectroscopy. Issue 9 (5th February 2016) - Popp, Alexander; Scheerer, David; Chi, Heng; Keiderling, Timothy A.; Hauser, Karin
Abstract: Turn residues and side‐chain interactions play an important role for the folding of β‐sheets. We investigated the conformational dynamics of a three‐stranded β‐sheet peptide ( D P D P) and a two‐stranded β‐hairpin (WVYY– D P) by time‐resolved temperature‐jump ( T ‐jump) infrared spectroscopy. Both peptide sequences contain D Pro–Gly residues that favor a tight β‐turn. The three‐stranded β‐sheet (Ac‐VFITS D PG KTYTEV D PG OKILQ–NH2 ) is stabilized by the turn sequences, whereas the β‐hairpin (SWTVE D PG KYTYK–NH2 ) folding is assisted by both the turn sequence and hydrophobic cross‐strand interactions. Relaxation times after the T ‐jump were monitored as a function of temperature and occur on a sub‐microsecond time scale, D P D P being faster than WVYY– D P. The Xxx– D Pro tertiary amide provides a detectable IR band, allowing us to probe the dynamics site‐specifically. The relative importance of the turn versus the intrastrand stability in β‐sheet formation is discussed. Abstract : Unravelling folding dynamics : Relaxation kinetics of β‐sheet peptides are monitored after a rapid temperature jump. The D Pro–Gly sequence promotes a tight turn. The interplay between turn‐ and sheet‐stabilizing residues is important for β‐sheet formation.